Investigation on the side effects of municipal solid waste incineration ashes when used as mineral addition in cement-based material*. Issue 2 (2nd April 2016) - Kim, Jinyoung; An, Jinwoo; Nam, Boo Hyun; Tasneem, Kazi Mahmuda
Abstract : The main focus of this study is the characterisation of the municipal solid waste incineration (MSWI) ashes and their influence on engineering properties of cement paste when part of Portland cement is replaced with ground MSWI ashes. Petrographic examinations were performed in order to identify chemical composition of ashes and to determine their contents. To evaluate the main side effect of ashes when used in cement, the creation of network of bubbles due to the presence of aluminium, ashes, and aluminium powder were submerged in high pH solution and the evolution of hydrogen gas was measured. Cement paste cylinders were cast with various amounts of mineral additions and their strength and durability were investigated. Analysis on the measured data demonstrated that the use of ashes as cement replacement has both beneficial and detrimental effects on the strength and durability caused by the filler effect and hydrogen gas development, respectively.